Hard-Disk Health Check. - Wagstaff, Jeremy (Far Eastern Economic Review, 2003)
The writer discusses the problem of computers that are running slowly and how this can be alleviated using a defragmentation program. He notes that the defragmenter program that comes with Windows XP is sufficient for individuals who are light users of their computers. For those who use their PC a lot, he recommends buying an extra program and suggests Raxco Software's PerfectDisk 2000, or Executive Software's Diskeeper.